Low refractive index gas sensing using a surface plasmon resonance fibre device - Kalli, Kyriacos; Allsop, Thomas P.; Neal, Ron M.; Davies, Edward M.; Mou, Chengbo; Bond, Peter R.; Rehman, Saeed Ur; Webb, David; Calverhouse, P.; Bennion, Ian (My University, 2010)
A series of surface plasmonic fibre devices were fabricated using multiple coatings deposited on a lapped section of a single mode fibre. Coupling from the guided mode to surface plasmons was promoted following UV laser irradiation of the coated region through a phase mask, which generated a surface relief grating structure. The devices showed high spectral sensitivities and strong coupling for low refractive indices as compared to other grating-type fibre devices. The plasmonic devices were used to detect the variation in the refractive indices of alkane gases with measured wavelength and coupling sensitivity to index of 3400 nm RIU -1 and 8300 dB RIU -1, respectively. As a demonstration of the performance of these gas sensors, a minimum concentration of 2% by volume of butane in ethane was achieved.
Keywords: Fibre optic sensors; Grating; Gas sensing; Surface plasmons